KOMPARASI KONDISI FINANCIAL DISTRESS BANK SYARIAH DI INDONESIA ANTARA TAHUN 2008 DAN TAHUN 2020 - Hayati, Izzah; Anwar, Saiful; Amrizal, Amrizal (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
Purpose – This study aims to finds out the comparisons between internal and external factors that influence financial distress condition of Islamic Banks in Indonesia between 2008 and 2020 based on artificial neural networks (ANNs). Design/metholodology/approach – The analysis consists of two main elements. First element is the identification and selection of significant macroeconomic variables to determine the level of Islamic bank financial distress. Second element is implementation of ANN model and evaluation the model based on simulated prediction of Islamic Banks financial distress in 2008 and 2020. Findings – The result of this research shows that there is a quite difference between Islamic Banks financial distress in 2008 and 2020. Financial distress of Islamic Banks in 2020 shows better prediction with 99.39 per cent accuracy than financial distress of Islamic Banks in 2008 with 97.38 per cent accuracy.